REGARDING SOME NEW WAVE DISTRIBUTIONS TO THE NONLINEAR BOGOYAVLENSKII EQUATION WITH CONFORMABLE DERIVATIVE - Panakhov, Etibar; Baskonus, Haci Mehmet; Kumar, Ajay; Bulut, Hasan; Kumar, Ashok (Baku State Univ, Inst Applied Mathematics, 2020)
[Abstract Not Available]
7th International Conference on Control and Optimization with Industrial Applications (COIA) -- AUG 26-28, 2020 -- ELECTR NETWORK
Keywords: Nonlinear Bogoyavlenskii Equation with Conformable; SGEM; Bright and Combined Dark-Bright Soliton Solutions; Complex New Travelling Wave Solution